Giudice e legge nelle dinamiche del biodiritto (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
Analysing the articles by Marta Tomasi and Simone Penasa, this contribution reflects on the role of the judiciary in the peculiar field of biolaw and, in particular, on its limits. The paper calls for a constitutionally and scientifically oriented biolaw, able to mediate between two extreme poles: the one of an almighty judge, on the one hand, and the one of an isolated decision maker, both left to their arbitrary adjudication of facts.
Keywords: Jurisdiction; Pluralism; Limits; Biolaw; Constitutionalism.